2013
DOI: 10.1016/s1470-2045(13)70448-0
|View full text |Cite
|
Sign up to set email alerts
|

The sex hormone system in carriers of BRCA1/2 mutations: a case-control study

Abstract: Carriers of BRCA1/BRCA2 mutations are exposed to higher titres of oestradiol and progesterone-known risk-factors for breast cancer. Higher titres of oestradiol in carriers are compatible with this hormone having a role in ovarian carcinogenesis in such women. Our findings could not be explained by differential contraceptive pill use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 25 publications
1
90
0
1
Order By: Relevance
“…Relative loss of PRB is seen with the development of atypia or malignancy and in women with germline mutations in BRCA1 or BRCA2 (Mote et al 2002). Interestingly, women with such mutations have double the serum progesterone levels compared to age matched WT controls although the significance of this finding is not known (Widschwendter et al 2013). …”
Section: Progesterone and Bcscsmentioning
confidence: 99%
“…Relative loss of PRB is seen with the development of atypia or malignancy and in women with germline mutations in BRCA1 or BRCA2 (Mote et al 2002). Interestingly, women with such mutations have double the serum progesterone levels compared to age matched WT controls although the significance of this finding is not known (Widschwendter et al 2013). …”
Section: Progesterone and Bcscsmentioning
confidence: 99%
“…Although the majority of BRCA1 tumours are estrogen receptor negative [4], oophorectomy [5] and tamoxifen [6] have been shown to reduce the risk of breast cancer, while oral contraceptive use increases the risk [7]. Interestingly, a recent study reported higher levels of serum estradiol and progesterone during the median luteal phase in premenopausal BRCA1/2 mutation carriers compared with premenopausal non-carriers, suggesting an important role of sex hormones in their predisposition to cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, unlike other studies, we only evaluate serum E2 level in the early follicular phase. Only basal E2 level measured on menstrual cycle days 2-5 has been validated as a standardized value [40], and late follicular or luteal phase E2 varies significantly based on individual variation and cycle length, limiting utility of the test outside the early follicular window [41]. A recent case-control study in cancer-free BRCA 1/2 mutation carriers found that luteal phase-not follicular phase-estradiol level is significantly higher in BRCA mutation carriers compared to non-carriers [42].…”
Section: Discussionmentioning
confidence: 99%